2014
DOI: 10.1148/rg.342130075
|View full text |Cite
|
Sign up to set email alerts
|

From the Radiologic Pathology Archives: Mass Lesions of the Dura: Beyond Meningioma—Radiologic-Pathologic Correlation

Abstract: Meningioma is the most common mass involving the dura, making it number one in the differential diagnosis for any dural-based mass; however, a variety of other neoplastic and nonneoplastic lesions also involve the dura. Knowledge of the dural anatomy can provide clues to the various processes that may involve this location. The neoplastic processes include both benign and malignant lesions such as hemangiopericytoma, lymphoma, solitary fibrous tumor, melanocytic lesions, Epstein-Barr virus-associated smooth mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 59 publications
2
67
0
6
Order By: Relevance
“…Another previous study suggested that 60% were located outside of the pleura (16), as SFTs have occurred on the falxcerebri, the convexity of the brain, the saddle area, the posterior cranial fossa, the dura mater, the encephala and in the CNS. SFTs often originate in the dura mater (17) and have been reported to be ubiquitous neoplasms of mesenchymal origin (18). SFT originating from the meninges are rare overall; the world literature on solitary fibrous tumors of the central nervous system (CNS) between August 1996 and July 2011 were reviewed, only 220 cases were reported in CNS, and 170 cases of SFT were originated from the meninges (19) ISFT is rare, accounting for ~0.6% of all intracranial tumors (13,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Another previous study suggested that 60% were located outside of the pleura (16), as SFTs have occurred on the falxcerebri, the convexity of the brain, the saddle area, the posterior cranial fossa, the dura mater, the encephala and in the CNS. SFTs often originate in the dura mater (17) and have been reported to be ubiquitous neoplasms of mesenchymal origin (18). SFT originating from the meninges are rare overall; the world literature on solitary fibrous tumors of the central nervous system (CNS) between August 1996 and July 2011 were reviewed, only 220 cases were reported in CNS, and 170 cases of SFT were originated from the meninges (19) ISFT is rare, accounting for ~0.6% of all intracranial tumors (13,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Чаще эти опухоли об-наруживаются у 30-и 40-летних пациентов, но до 10 % случаев диагностируются у детей [9]. Несколько чаще с ними сталкиваются пациенты мужского пола: 1,4 : 1 [5,8].…”
Section: лучевая терапия менингеальных гемангиоперицитомunclassified
“…Головные боли, судорожные приступы, очаговая неврологическая симптоматика -все это может быть симптомами болезни [9]. Вдобавок, до 20 % ге-мангиоперицитом способны метастазировать отда-ленно -обычно в печень, легкие, кости скелета [5,7,9], но также встречаются редкие варианты метастазиро-вания, в частности в почки [10,11].…”
Section: лучевая терапия менингеальных гемангиоперицитомunclassified
“…Distinct immunohistochemical features characterize these tumours which include diffuse CD34 positivity and epithelial membrane antigen negativity [34] (Figure 5). Some tumours may show hypocellular areas with profuse extracellular collagen deposition alternating with hypercellular areas [35] . MRI reveals heterogeneous appearance of SFTs on T2 weighted images.…”
Section: Solitary Fibrous Tumourmentioning
confidence: 99%